2020
DOI: 10.1056/nejmoa1915905
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Dose Zinc for Childhood Diarrhea — A Randomized, Multicenter Trial

Abstract: Background The WHO recommends 20 mg/day of supplemental zinc for children with acute diarrhea for 10-14 days; in previous trials this dosage improved diarrhea but increased vomiting. Methods We randomly assigned 4500 children ages 6 to 59 months in India and Tanzania with acute diarrhea to one of three arms (5, 10 or 20 mg zinc sulfate for 14 days). The three primary outcomes were diarrhea duration >5 days and mean number of stools (tested for non-inferiority), and vomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…93 In a recent study conducted in India and Tanzania, 4500 children aged 6–59 months with acute diarrhoea were randomized to receive 5 mg, 10 mg and 20 mg of zinc sulphate orally for 14 days. 94 The mean number of diarrhoeal stool was 10.7, 10.9 and 10.8 in the 20-mg, 10-mg and 5-mg groups, respectively. Vomiting within 30 minutes after administration of zinc sulphate occurred in 19.3%, 15.6% and 13.7% of children in the 20-mg, 10-mg and 5-mg groups, respectively.…”
Section: Managementmentioning
confidence: 88%
See 1 more Smart Citation
“…93 In a recent study conducted in India and Tanzania, 4500 children aged 6–59 months with acute diarrhoea were randomized to receive 5 mg, 10 mg and 20 mg of zinc sulphate orally for 14 days. 94 The mean number of diarrhoeal stool was 10.7, 10.9 and 10.8 in the 20-mg, 10-mg and 5-mg groups, respectively. Vomiting within 30 minutes after administration of zinc sulphate occurred in 19.3%, 15.6% and 13.7% of children in the 20-mg, 10-mg and 5-mg groups, respectively.…”
Section: Managementmentioning
confidence: 88%
“…The authors concluded that lower doses of zinc have non-inferiority efficacy for the treatment of children with acute diarrhoea and have less vomiting than the standard 20-mg dose. 94 A 2016 Cochrane review found that zinc supplementation may be of benefit in the treatment of diarrhoea in children aged 6 months and older in areas where the prevalence of zinc deficiency or malnutrition is high. 95 The current evidence does not support the routine use of zinc supplementation in children less than 6 months of age, in well-nourished children and children in areas at low risk of zinc deficiency.…”
Section: Managementmentioning
confidence: 99%
“…The SDG-3 specifically targets to reduce under-five mortality at least by 25 per 1,000 live births [3] and therefore more emphasis should be given for the reduction of diarrhea related under-five deaths. Prompt and adequate management of diarrhea is the principal factor of targeted approach for reduction of diarrheal deaths [4]. World Health Organization (WHO) recommended oral rehydration solution (ORS) and oral zinc therapy in addition to frequent breast feeding, and home available fluids are the mainstay of management of diarrhea [5].…”
Section: Cooked Green Banana In Hospitalized Children With Acute Waterymentioning
confidence: 99%
“…Zinc deficiency has been linked to impaired child growth and is common in children living in settings where dietary diversity and consumption of animal-source foods are limited [ 1 ]. Therapeutic zinc supplementation reduces the duration of diarrhea in children [ 3 ] and is part of the World Health Organization (WHO) Integrated Management of Childhood Illness guidelines for treatment of diarrhea [ 4 ]. Preventive zinc supplementation provided as a stand-alone dispersible tablet, or via home fortification as multiple micronutrient powders (MNPs), has been considered a potential strategy to prevent zinc deficiency in low- and middle-income countries (LMICs).…”
Section: Introductionmentioning
confidence: 99%